A retrospective study on the physical growth of twins in the first year after birth - Pan, Ting; Huang, Yanru; Cheng, Qian; Chen, Li; Hu, Yan; Dai, Ying; Liu, Xiao; Jiang, Zhiyang; Zhong, Yuanfeng; Zhang, Zhanzhan; Chen, Qian; Zhang, Qian; et al. (Frontiers in Nutrition, 2023)
Objectives This study analyzed the physical growth of small for gestational age (SGA) and appropriate for gestational age (AGA) twins up to one year after birth. Methods Weight, length, and head circumference data of 0–1 year-old twins were collected from the Child Health Care System from 2010 to 2019. Physical data were presented as Z-scores. Five parameters – growth level of weight, body length, head circumference, growth velocity, and body proportion (weight for length) were compared in twins. Results A total of 3,909 cases were collected (22.61% SGA, 77.39% AGA). 1. In both groups, WAZ (Weight for age z-score), HCZ (Head circumference for age z-score), and LAZ (Length for age z-score) increased more rapidly in the first 6 months. By one year of age, WAZ, HCZ, and LAZ had reached the normal range, but none had reached the average level of normal singleton children. 2. The mean values of WAZ, HCZ, and LAZ in the AGA group were between −1 and 0, and between −2 and − 1 in the SGA group, in the first year after birth. The SGA group lagged significantly behind the AGA group. The LAZ score of SGA and AGA was lower than the WAZ and HCZ scores. 3. The proportion of preterm AGA was the largest in twins, and the growth rate of preterm AGA was the fastest. Preterm twins had greater growth potential than term twins. However, the growth level of preterm SGA was always low. 4. The WFLZ (Weight for length z-score) in each group was approximately close to 0. The WFLZ of SGA was smaller than that of AGA twins at most time points. After 4 months of age, the WFLZ of twins had a downward trend. The WFLZ of preterm SGA approached −1 at approximately 1 year old. Conclusion The physical growth of SGA and AGA in twins in the first year can reach the normal range but cannot reach the average level of normal singleton children. More attention should be paid to SGA in twins, especially preterm SGA. We should give proper nutritional guidance after 4 months of age to ensure the appropriate body proportion (weight for length) of SGA in twins. Clinical trial registration www.chictr.org.cn, CTR2000034761.